Quality Changes in the Adductor Muscle of Ezo Giant Scallop Mizuhopecten yessoensis (Jay, 1857) during Refrigerated Storage - Hiroko Seki (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2021)
Recently, the popularity of scallops consumption and the preference to eat them raw have been increasing worldwide. Therefore, maintaining its freshness and quality is important. It is necessary to investigate the changes in quality, particularly umami-related component parameters and perform a comprehensive evaluation to assess scallop quality over time. In this study, the distinction in the abundance of microorganisms, K value, pH, color value, glycogen content, and ATP-related compound levels (i.e., ATP, ADP, AMP, IMP, HxR, Hx, and glutamic acid levels) were investigated to determine the quality of Ezo giant scallops. The parameters were evaluated every day for six days at 4°C post mortem of the scallops. The total viable aerobic count of marine bacteria increased from 1 to 3 log CFU/g over six days, and the K value increased sharply from 18% on day 2 to 66% on day 4. The pH decreased from 7.0 on day 0 to 6.0 on day 3, but the color value did not change during the six days of observation. The AMP content increased over three days and then decreased during the last three days of storage. IMP was not detected; meanwhile, the glycogen and glutamic acid levels were stable during the observation. Based on these results, the best recommendation is to serve the refrigerated scallops as sashimi for not more than two days and cook by the third day to preserve the quality.